Determinants of Women’s Empowerment and Household Poverty Reduction in Imbulpe DS Division, Sri Lanka - Rathnachandra, S.D. Dilini; Malkanthi, S.H. Pushpa (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2021)
Women empowerment and poverty reduction are interrelated key driving forces to achieve the sustainable development of a country. However, most of the women farmers in rural areas have lack of access to adequate assets and resources, credit facilities and freedom of decision making within the households. Therefore, women empowerment is a timely important requirement to reduce the household poverty among them. This study was conducted to identify the determinants of empowerment of women farmers and also roles of them in reduction of poverty in Imbulpe Divisional Secretariat (DS) Division in Sri Lanka. In this study, 238 women farmers were selected using simple random sampling method, from purposively identified seven Grama Niladhari (GN) divisions in this area. Primary data was gathered from a field survey using a pre-tested, self-administered questionnaire from May to July 2019. Descriptive statistics and chi-square analysis were used as the statistical methods in data analyzing process. The result revealed that, age, education, monthly income of the respondents, economic resource accessibility, participation in decision making and freedom of mobility act as the determinants of empowerment of women farmers. The moderately significant positive nature of relationship was showed between the age of the women farmers and their role in poverty reduction. And also, the level of education, monthly income, economic resources accessibility of the respondents and participation of decision making within the household of the women farmers were showed moderately significant positive relationship with their role in poverty reduction. Therefore, encourage women farmers as rural entrepreneurs while performing their farming practices to earn additional income, enhance economic resource accessibility and motivate women farmers to express their ideas for enhance the active participation in the household decision making process are timely important requirements to empower women farmers and enhance their role in poverty reduction.